(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Features of livestock houses designing for rural (farm) enterprises with observance of sanitary standards have been described; expensiveness of the design phases, construction and installation works and electricity generation equipment in such buildings is emphasized. Foreign experience in solar cell batteries application has been analyzed. Advantages and disadvantages of the renewable power sources setting up have been determined, particularly concerning the first few years of operation. The dynamics of the energy-intensive equipment installation at farm enterprises of Ukraine has been analyzed, a trend of implementing innovative technologies as an autonomous, maximally independent energy supply source, has been detected. The environmental safety of such energy supply solution and its installation efficiency in any region is emphasized. The possibility is considered for alternative energy supply sources application and energy supply independence of cooperated livestock houses at farm enterprises, particularly under the conditions of persistent reduction in prices for photoelectric modules and persistent growth of gas and electricity rates. Keywords: livestock house, farm enterprise, natural energy sources, solar cell batteries.